An evolutionary approach to the use of petri net based models : from parallel controllers to Hw/Sw codesign - Machado, Ricardo J. (2000)
The main purpose of this article is to present how Petri Nets (PNs) have been used for hardware design at our research laboratory. We describe the use of PN models to specify synchronous parallel controllers and how PN specifications can be extended to include the behavioural description of the data path, by using object-oriented concepts. Some hierarchical mechanisms which deal with the specification of complex digital systems are highlighted. It is described a design flow that includes, among others, the automatic generation of VHDL code to synthesize the control unit of the system. The use of PNs as part of a multiple-view model within an object-oriented methodology for hardware/software codesign is debated. The EDgAR-2 platform is considered as the reconfigurable target architecture for implementing the systems and its main characteristics are shown.